FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA PADA REMAJA KARANG TARUNA WIJAYA KUSUMA KELURAHAN KRAMAS KECAMATAN TEMBALANG KOTA SEMARANG - Cicik Harini; Yulianeu Yulianeu (Universitas Islam Nahdlatul Ulama Jepara, 2018)
The causes of unemployment are because of unbalancing between population of people and employment. The availability of work field is created by entrepreneurs, such as in development countries, they have minimal 2% entrepreneurs. The way to enhance entrepreneurship, it needs to change mindset through education including research of affective, educative, and environment toward The resuls of this study shows that education coefficiency is 0.32 with p = 0.04 which means that education variables have a positive effect on entrepreneur interest. While the environment co efficiency is 0.66 with p